Aiding the versatility of simple ammonium ionic liquids by the synthesis of bioactive 1, 2, 3, 4-tetrahydropyrimidine, 2-aminothiazole and quinazolinone derivatives. (29th March 2021) - Kakati, Praachi; Singh, Preeti; Yadav, Priyanka; Awasthi, Satish Kumar
Abstract : The work presented in this paper showcases the utility of ionic liquids in the synthesis of tetrahydropyrimidinone, 2-aminothiazole and quinazolinone derivatives in a sustainable protocol. Abstract : Simple ammonium ionic liquids [ILs] are efficient, green, environmentally friendly catalysts in promoting the Biginelli condensation reaction, Hantzsch reaction and Niementowski reaction to afford 1, 2, 3, 4-tetrahydropyrimidine, 2-aminothiazole and quinazolinone derivatives respectively by eliminating the need for harmful volatile organic solvents. These [ILs] are air and water stable, easy to prepare and cost-effective. The effects of the anions and cations present in [IL] on reactions were investigated. The results clearly indicated that the Biginelli condensation reaction, Hantzsch reaction and Niementowski reaction were heavily influenced by the acidity of [IL], and among various ammonium ionic liquids, [Et3 NH][HSO4 ] showed the best catalytic activity. Furthermore, [IL] could be easily separated and reused with a slight loss of its activity. This technique provided a good alternative way for the industrial synthesis of 1, 2, 3, 4-tetrahydropyrimidinones, 2-aminothiazoles and quinazolinones. The present processes are eco-friendly methods for the synthesis of these derivatives authenticated by several green parameters, namely, E -factor, process mass intensity, reaction mass efficiency, atom economy, and carbon efficiency.